Arbitrating under the 2020 LCIA rules a user's guide - Scherer, Maxi (Kluwer Law International B. V., 2021)
The London Court of International Arbitration (LCIA), the oldest of all major arbitral institutions, has, since its establishment well over a century ago, embodied the ideals that underlie the arbitral alternative and set its face against undue delay, soaring cost, complexity, and acrimony. Today, the LCIA administers cases arising under any system of law in any venue worldwide. Underscoring the institution's international nature, and over 80% of parties in pending LCIA cases today are not of English nationality. This highly practical and user-friendly guide provides not only a thorough analysis of the 2020 LCIA Rules but also a comprehensive explanation of the basic principles governing LCIA arbitration, along with an in-depth analysis of complex issues that may arise in the course of LCIA proceedings. Among the new and revised rules affecting LCIA practice and procedure described in detail include the following: use of technology, accommodating virtual conferencing, remote hearings and electronically signed awards, as well as confirming the primacy of electronic communication with the LCIA; tools to expedite proceedings, including the possibility of early dismissal determinations; explicit consideration of data protection; issues relating to bribery, corruption, terrorist financing, fraud, tax evasion, money laundering and/or economic or trade sanctions; streamlined accommodations for consolidation, composite Requests and concurrent conduct of arbitrations; conduct of authorised representatives of a party; requirements for appointment and removal of tribunal secretaries; and revised schedules of arbitration and mediation costs. The twenty-six chapters of the book provide references to essential national court judgments, statutory provisions, up-to-date statistics, and bibliographical sources on LCIA arbitrations. The 2020 LCIA Rules reflect the most sophisticated current modifications of arbitral procedure, fully aligned with the needs of current global commercial activities. For this reason, and because many companies worldwide include LCIA arbitration clauses in their agreements, this book is invaluable to business executives and corporate counsel as well as to scholars of alternative dispute resolution.